Functional Condition of the Lower Limb Muscles and Their Spinal Centers at the Knee Joint Pathology - Fedyanin, A. O., (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The purpose of this work is the research of parameters of electric activity of muscles of a thigh and a shin and functional condition of their spinal centers at healthy subjects and gonarthrosis patients. Materials and Methods: By methods of global and electrostimulation myography, we have conducted examination by quadriceps femoris (QFM) and triceps surae at healthy examinees and gonarthrosis patients. Results: It is established that pathological process in a knee joint changes a functional condition of the neuromotor apparatus of muscles of the lower limbs. Average amplitude of gonarthrosis was significantly lower than the caused electric activity of these muscles for patients than for healthy examinees. Patients had thresholds of motor (M) and reflex (N) responses higher, and their maximum amplitude as well as the relation of Hmax/Mmax it is much lower. Conclusion: Thus, it is established that nociceptive influence from the affected joints slows down the activity of muscles and their spinal centers. Most strongly, these influences are shown on muscles, the extensor participating in direct activity of a joint, i.e. on the QFM, but can affect also other muscles.